Room light anodic etching of highly doped n-type 4 H-SiC in high-concentration HF electrolytes: Difference between C and Si crystalline faces - Gautier, Gael (Springer, 2012)
In this paper, we study the electrochemical anodization of n-type heavily doped 4 H-SiC wafers in a HF-based electrolyte without any UV light assistance. We present, in particular, the differences observed between the etching of Si and C faces. In the case of the Si face, the resulting material is mesoporous (diameters in the range of 5 to 50 nm) with an increase of the ‘chevron shaped’ pore density with depth. In the case of the C face, a columnar morphology is observed, and the etch rate is twice greater than for the one for the Si face. We've also observed the evolution of the potential for a fixed applied current density. Finally, some wafer defects induced by polishing are clearly revealed at the sample surfaces even for very short etching times.